The significance of physical activity in the prevention of osteoporosis in older adults - Hubert Stachowicz; Joanna Mazurek; Monika Adamczyk; Miłosz Podrażka; Justyna Lenart; Aleksandra Baran; Magdalena Piotrowska-Żołnierczuk; Ewelina Flegiel; Magdalena Ptasznik; Norbert Stachowicz (Kazimierz Wielki University, 2024)
Introduction and objective Osteoporosis is a disorder that leads to a decrease in bone mass, accompanied by a disruption in bone structure, resulting in an increased risk of bone fractures. It affects a large number of people worldwide and constitutes a significant social and economic problem. It primarily affects older individuals, especially postmenopausal women. Fractures associated with osteoporosis diminish the quality of life. Osteoporosis often remains asymptomatic and is difficult to diagnose, typically identified incidentally following a low-energy fracture. Diagnosis of osteoporosis involves measuring bone mineral density using dual-energy X-ray absorptiometry (DEXA). Osteoporosis is diagnosed when bone mineral density is found to be more than 2.5 standard deviations (SD) below the mean bone mineral density of healthy young adults with peak bone mass. Modifiable risk factors for osteoporosis include lack of physical activity, calcium deficiency in the diet, and alcohol consumption. Review methods The article was based on scientific papers retrieved from the PubMed website and scientific literature. The focus was on papers from 2016 to 2024. Articles written in English were utilized. Brief description of the state of knowledge Physical activity encompasses any muscular movement that increases energy expenditure beyond the resting metabolic rate, including weight-bearing exercises, strength training, high-intensity strength exercises, and balance and mobility training. Weight-bearing exercises yield the best results in osteoporosis prevention, recommended to be performed three times a week. Summary Physical activity is a scientifically proven preventive factor against osteoporosis, reducing the frequency of falls and increasing bone mineral density. Initiating physical activity at a young age yields significant benefits for bone strength.